Association of Pregnancy Complications with Endometrial or Ovarian or Breast Cancer: A Case Control Study - Lin Cheng Han; Henry W. C. Leung; Heng-Jun Lin; John Hang Leung; Agnes L. F. Chan (Medicina)
Background and Objectives: The relationship between pregnancy complications and the risk of gynecological and breast cancer remains inconclusive, with limited research available. This study aimed to determine whether pregnancy complications, including preeclampsia, gestational diabetes mellitus (GDM), large for gestational age (LGA), or intrauterine growth restriction (IUGR) are associated with the development of endometrial cancer (EC), ovarian cancer (OC), or breast cancer (BC). Materials and Methods: This was a population-based case–control study linked to the National Health Insurance Research Database from 2008 to 2020, using ICD codes to identify parous gynecological cases (n = 6714). The propensity score matching method was used to match control groups (n = 1,153,346). Multivariable logistic regression models were used to determine the association between EC, OC, BC risk and pregnancy complications. Results: In adjusted multivariable logistic regression models, women with a history of preeclampsia did not have a significantly increased risk of endometrial, ovarian, or breast cancer compared to controls. Although women with GDM complications had a significantly increased risk of breast cancer, the increased risk of EC or OC was not significant. The risk of BC in women with a history of IUGR or LGA was not significant, whereas risk statistics for EC or OC in women with a history of IUGR or LGA could not be shown because of the small sample size. Conclusions: GDM is associated with BC risk. Future studies should aim to determine whether there is a causal relationship. Therefore, cancer screening is warranted in women with GDM.